PROTEIN RESIDUE (CIEP) ANALYSIS OF A SAMPLE FROM WAPITI RIVER CROSSING, SITE GfQu-30, GRANDE PRAIRIE NO. 1 COUNTY, ALBERTA, CANADA - Cummings, Linda Scott (2020)
One Clovis point midsection and a soil control sample recovered from site GfQu-30 in Grande Prairie No. 1 County were submitted for protein residue analysis to identify any proteins present on the point.